O desenvolvimento da compreensão leitora e da consciência textual : um estudo com alunos de 6° e 9° anos do ensino fundamental II - Carvalho, Roberta Silveira (2021)
This master’s thesis finds support in the field of Psycholinguistics; its general goal is to contribute to psycholinguistic studies relating to how much is known about reading comprehension and textual awareness of Elementary School II students, by investigating their development in this school period. The research sample consisted of 30 subjects (15 from the 6th grade and 15 from the 9th grade), from a public state school in Porto Alegre. They answered the instruments of Reading Comprehension and Textual Awareness, and Reading Habits. The Reading Comprehension and Textual Awareness instrument, which consisted of a single text, aimed to assess the students’ performance concerning these topics, by comparing their evolution from 6th to 9th grade. The data from the Reading Habits instrument was collected face-to-face, whereas data collection from the Reading Comprehension and Textual Awareness instrument was based on a remote teaching model, via Google Meet platform, due to the pandemic. Reading teaching materials used by Portuguese teachers from the selected school, handed out in person to students, were also used as data for the analysis. The results showed a strong positive correlation among reading comprehension, textual awareness and reading habits, considering the reading teaching materials used by the teachers. In relation to school years, an increase of 1.1 points in the 9th grade, in comparison to the 6th grade, was observed. Subjects from the 6th grade scored 7 out of 10 correct answers in the Reading Comprehension Instrument, while 9th graders scored 8.1. Regarding textual awareness, an increase of 0.77 points in the 9th grade was verified, when compared to the 6th grade, which had a score of 3.13 points, as 9th grade students had a score of 3.90 points. Based on these results, it can be concluded that 9th graders showed higher reading performance than 6th grade students, possibly due to the longer time of exposure to the teaching of reading.